Long-term effects of dam operations for water supply to irrigation on downstream river reaches. The case of the Ribb River, Ethiopia. Issue 4 (2nd October 2021) - Mulatu, Chalachew A.; Crosato, Alessandra; Langendoen, Eddy J.; Moges, Michael M.; McClain, Michael E.
ABSTRACT: This work investigates the applicability of an analytical method for quick assessments of the long-term morphological effects of different dam operations on downstream river reaches with the idea to apply the method in feasibility studies to identify the least morphologic-impacting operation scenario. The Ribb River (Ethiopia) is used as a study case. The analytical method estimates the idealized, new equilibrium of the river bed profile without considering the duration of the morphological evolution. We apply the analytical method distinguishing sand-bed from gravel-bed reaches. The outcome of the analytical method is compared to that of a calibrated one-dimensional river morphology computer model. The analytical method overestimated the morphological changes compared to the one-dimensional model. By establishing the upper limits of the impact, the analytical method identifies a theoretical maximum river bed degradation near the base of the dam. If all sediment is trapped in the reservoir, the method allows distinguishing the effects of different dam operation scenarios, but only for gravel-bed river reaches. However, the method can also be applicable for sand-bed reaches if there is sediment input from the upper reaches. Further research works should be done to validate both methods if they indeed allow to detect the least impacting scenario, considering that data showing the effects of long-term dam operations on the downstream river reaches are lacking.